A quest for global peace Rotblat and Ikeda on war, ethics, and the nuclear threat - Rotblat, Joseph 1908-2005; Ikeda, Daisaku (I.B. Tauris Distributed in the U.S.A. by Palgrave Macmillan, 2007)
One of the 'inventors' of the nuclear bomb, Sir Joseph Rotblat soon turned away from weapons research to make a principled stand against the dangers of nuclear proliferation. This work contains a series of dialogues between Rotblat and Daisake Ikeda, the leader of the world's largest and most influential Buddhist organisation.